2011
DOI: 10.4028/www.scientific.net/aef.2-3.876
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Thermal Loading on the Dynamic Response of Thin-Walled Structure under Thermo-Acoustic Loading

Abstract: Abstract. Future flight vehicle structures will encounter severe loading conditions, a combination of aerodynamic, thermal, acoustic and mechanical loads. Although the analysis methods for responses of structures under acoustic loads have been developed to some extent, but with thermal loads considered, the responses show fundamental differences, which complicate the analysis immensely. It was reported that hypersonic flight may give rise to surface temperature as high as o 3000 F and intense noise whose overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Generally, the nonlinear vibration for thermal bucked structure is considered to calculate the thermal-acoustic response [7][8][9][10][11]. The response of the post thermal buckling plate can be seen as a shell problem, as the FEM is used to solve the shell problem.…”
Section: Motion Equations Of the Thin-walled Plate Under Thermal-acoumentioning
confidence: 99%
“…Generally, the nonlinear vibration for thermal bucked structure is considered to calculate the thermal-acoustic response [7][8][9][10][11]. The response of the post thermal buckling plate can be seen as a shell problem, as the FEM is used to solve the shell problem.…”
Section: Motion Equations Of the Thin-walled Plate Under Thermal-acoumentioning
confidence: 99%
“…In China, Professor Sha Yun-dong and his coworkers have already done lots of research work about thermal-acoustic response and fatigue life of flight vehicles thin-walled structures, and published numbers of literatures [13][14][15][16][17][18]. For example, in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental work on nonlinear responses of curved panels under acoustic excitations was done by Holehouse [7], Ng and White [8]. Nonlinear random response and fatigue life of thin-wall flat plates subjected to combined thermo-acoustic loads using PDE/Galerkin method and finite element method are investigated by Yundong Sha [9][10][11][12], and it is shown that snap-through motion will appear due to the critical thermal buckled characteristics under high intensity acoustic random loading, and the fatigue life will decrease with the increase of thermal load before the critical thermal buckled temperature. This paper wok on nonlinear response of thin-walled structures subjected to thermal loads with a linear temperature gradient and acoustic loads, the thermal buckled temperature and modal frequencies of thin-walled structures with liner temperature gradient are calculated, and the displacement and dynamic stress responses of thin-walled structures are obtained.…”
Section: Introductionmentioning
confidence: 99%